Perovskite Single Crystals by Vacuum Evaporation Crystallization - Dong Liu; Xianyuan Jiang; Hao Wang; Hao Chen; Ying‐Bo Lu; Siyu Dong; Zhijun Ning; Yong Wang; Zhongchen Wu; Zongcheng Ling (Advanced Science, 2024)
Abstract Perovskite single crystals have attracted tremendous attention owing to their excellent optoelectronic properties and stability compared to typical multicrystal structures. However, the growth of high‐quality perovskite single crystals (PSCs) generally relies on temperature gradients or the introduction of additives to promote crystal growth. In this study, a vacuum evaporation crystallization technique is developed that allows PSCs to be grown under extremely stable conditions at constant temperature and without requiring additives to promote crystal growth. The new method enables the growth of PSCs of unprecedented quality, that is, MAPbBr3 single crystals that exhibit an ultranarrow full width at half maximum of 0.00701°, which surpasses that of all previously reported values. In addition, the MAPbBr3 single crystals deliver exceptional optoelectronic performance, including a long carrier lifetime of 1006 ns, an ultralow trap‐state density of 3.67 × 109 cm−3, and an ultrahigh carrier mobility of 185.86 cm2 V−1 s−1. This method is applicable to various types of PSCs, including organic–inorganic hybrids, fully inorganic structures, and low‐dimensional structures.